EVALUASI RENCANA KERJA PEMERINTAH (RKP) 2017 PRIORITAS NASIONAL BIDANG PENDIDIKAN: Peningkatan Akses, Kualitas, Relevansi, dan Daya Saing Pendidikan - Yenni Anggrayni (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
Performance Evaluation of Government Work Plan (RKP) 2017 aims to find out the results of the achievement of development performance, especially the achievement of PN as material for the formulation and improvement of policies/ programs / activities, especially in the field of education with PN. Increasing Access, Quality, Relevance, and Competitiveness of Education achievement of development performance, especially the achievement of PN as material for formulation and improvement of policies / programs  / activities, especially in the field of education with PN Improving Access, Quality, Relevance, and Educational Competitiveness. The research method used is gap analysis, namely performance measurement that compares the realization with a predetermined target, as well as an independent assessment of the implementing K / L. In general, National Priorities for Improving Access, Quality, Relevance and Competitiveness in Education show good achievements until 2017. Problems in implementing PN Increasing Access, Quality, Relevance, and Competitiveness Education can be categorized into three groups, namely institutional issues, budget, and HR. The follow-up was carried out, namely reallocating the budget, adjusting changes in the management authority of high schools and vocational schools, refocusing programs and activities, and optimizing HR utilization.